SERBIA – ZONE OF POVERTY AND SOCIAL EXCLUSION - Petar Veselinović; Vladimir Mićić; Dalibor Miletić (Ekonomika Poljoprivrede (1979), 2012)
A fall in the populations living standard and the growth of poverty in Serbia are, first of all, the consequence of a significant decrease in the economic activity. The problem of poverty and social exclusion is additionally intensified and made bigger by the world economic crisis influence. The subject of the paper is the analysis of the current situation, which is crucially significant for solving the stated problems, i.e. suppressing negative phenomena which are the cause of poverty and social exclusion. The paper is aimed at gaining an insight into basic causes responsible for poverty in Serbia as the basis for the determination of necessary measures and activities for problem solving. The poverty indicators used in the analysis are the poverty rate, poverty depth and severity. Solving poverty problems is the priority task Serbia has to deal with on its way to integrate into the EU and it requires reaching new strategies for reducing poverty as well as its efficient implementation.